Analisis Makna Kandoushi Dalam Komik Doraemon Volume1 - Muhammad Munadhil Shoib; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
This research discusses the types and meanings of kandoushi contained in the Doraemon comic volume 1, because it is motivated by the difficulty of understanding the meaning of kandoushi contained in a conversation so that it can cause misunderstanding in the interpretation of meaning. This research is a qualitative research with descriptive method. The data in this study are words or sentences containing kandoushi spoken by the characters in the Doraemon comic volume 1. The instrument in this research is the researcher himself. In this research, 34 kandoushi data were found. Of the 34 kandoushi data, the author found 4 types of kandoushi which are divided into 18 kandoushi kandou, 5 kandoushi outou, 10 kandoushi yobikake, and 1 kandoushi aisatsugo. Kandoushi kandou consists of waa, a', e', are, nani, maa, aa, and hahaha, kandoushi outou consists of sou, iyadayo, namely, kandoushi yobikake consists of oi, ya, you, kora and saa, kandoushi aisatsugo consists of tadaima. Of the four types of kandoushi, the type that appears the most is kandoushi kandou. This is because there are many unexpected events caused by Doraemon's tools from the future, Doraemon introduces and uses the tools in the magic bag to the characters there. So that it makes a lot of dialog that contains the meaning of amazement, surprise, wonder and happiness. Therefore, this is the reason why kandoushi kandou is found more than other types of kandoushi.